Radioluminescence of rare-earth doped potassium yttrium fluorides crystals - Molina, Pablo Fernando (2011)
The radioluminescence (RL) properties of K2YF5 crystals doped with Ce3+, Tb3+ and Dy3+ under ionizing irradiation excitation have been studied for the first time. The main objective of this work has been to assess the feasibility of using these crystals as detectors for fiberoptic radioluminescent dosimetry. In particular, it has been found that the RL intensity from both K2YF5:Tb (10%) and K2TbF5 is comparable to that from a commercial Al2O3:C crystal. Longer wavelength emission from these fluorides makes simple optical filtering technique possible to use in order to avoid the stem effect. Afterglow decay times for these fluorides have been found to be similar to that for Al2O3:C and, in particular, K2TbF5 does not show longer afterglow decay time compared to Al2O3:C.